A zebrafish model of crim1 loss of function has small and misshapen lenses with dysregulated clic4 and fgf1b expression - Le, Tien; Htun, Stephanie; Pandey, Manoj Kumar; Sun, Yihui; Magnusen, Albert Frank; Ullah, Ehsan; Lauzon, Julie; Beres, Shannon; Lee, Chung; Guan, Bin; Hufnagel, Robert B.; Brooks, Brian P.; et al. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionHeterozygous deletions predicting haploinsufficiency for the Cysteine Rich Motor Neuron 1 (CRIM1) gene have been identified in two families with macrophthalmia, colobomatous, with microcornea (MACOM), an autosomal dominant trait. Crim1 encodes a type I transmembrane protein that is expressed at the cell membrane of lens epithelial and fiber cells at the stage of lens pit formation. Decreased Crim1 expression in the mouse reduced the number of lens epithelial cells and caused defective adhesion between lens epithelial cells and between the epithelial and fiber cells.MethodsWe present three patients with heterozygous deletions and truncating variants predicted to result in haploinsufficiency for CRIM1 as further evidence for the role of this gene in eye defects, including retinal coloboma, optic pallor, and glaucoma. We used Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/Cas9 to make a stable Danio rerio model of crim1 deficiency, generating zebrafish that were homozygous for a 2 basepair deletion, c.339_340delCT p.Leu112Leufs*, in crim1.ResultsHomozygous, crim1−/− larvae demonstrated smaller eyes and small and misshapen lenses compared to controls, but we did not observe colobomas. Bulk RNA-Seq using dissected eyes from crim1−/− larvae and controls at 72 h post fertilization showed significant downregulation of crim1 and chloride intracellular channel 4 (clic4) and upregulation of fibroblast growth factor 1b (fgf1b) and complement component 1, q subcomponent (c1q), amongst other dysregulated genes.DiscussionOur work strengthens the association between haploinsufficiency for CRIM1 and eye defects and characterizes a stable model of crim1 loss of function for future research.